Functional and Emotional Features Studies on Traditional Indonesian Instant Food Packaging - Monica Hartanti; Nina Nurviana (Journal of Visual Art and Design, 2020)
Food technology and packaging create opportunities for Indonesian SMEs to sell traditional dishes for instant cooking. Such products require a fitting packaging design. The purpose of this study was to find out verbal and visual design elements that have functional and emotional appeal that are suitable for the packaging of instant traditional Indonesian food. This study used a combined qualitative and quantitative method, measuring the respondents' opinions using a 5-point Likert scale. According to the results, the packaging of instant traditional Indonesian food brands is mostly functional but not unique. To make the appearance of the products stand out more and have more emotional appeal, three things can be applied to the packaging design: firstly, unusual colors and shapes to create a unique impression; secondly, a conventional image rather than a modern image; and thirdly, visual and verbal icons referring to the origin of the traditional dish that are still popular to create a familiar image.